Investigating the Feasibility of a CMOS Camera in Developing a Shortwave Near Infrared Spectroscopy - Chia, Kim Seng; Yap, Xien Yin; Gamal Al-kaf, Hasan Ali (International Journal of Integrated Engineering, 2020)
Near infrared (NIR) sensing technology has been widely implemented in various areas replace conventional wet chemistry analysis due to its non-invasive, green and rapid measurement features. A combination of NIR LEDs and photodiodes shows the possibility to reduce the financial barrier to carry out NIR research. However, there is a challenge to detect and remove unwanted signals. Therefore, this study aims to investigate the feasibility of a CMOS camera in developing a shortwave near infrared spectroscopy. Firstly, a slit, a NIR grating, and a CMOS camera were positioned and shielded in a black aluminum chassis. A total of six different parameters of the camera were investigated in this study, i.e. the exposure level, gain, white balance, brightness, sharpness, and saturation. Findings suggest that the CMOS camera with the optimal values of the exposure level and the gain could produce a good quality of NIR spectrum.